Money Laundering and Financial Means of Organized Crime: Some Preliminary Empirical Findings - Friedrich Schneider
After giving a short literature review, the paper tries a quantification of the volume of money laundering activities, with the help of a MIMIC estimation procedure for the years 1995 to 2006 for 20 highly developed OECD countries. The volume of laundered money was 273 billions USD in the year 1995 for these 20 OECD countries and increased to 603 billions USD in 2006. The overall turnover in organized crime had a value of 595 billion USD in 2001 and increased to 790 billion USD in 2006. These figures are very preliminary but give a clear indication how important money laundering and the turnover of organized crime is nowadays.Definition and stages of money laundering, volume of money laundering, MIMIC estimation, financial means of organized crime